2013
DOI: 10.4084/mjhid.2013.044
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor in Children With Thalassemia Major PDF

Abstract: BackgroundThe β-Thalassemia syndromes are the most common hereditary chronic hemolytic anemia due to impaired globin chain synthesis. Vascular endothelial growth factor (VEGF) plays several roles in angiogenesis which is a crucial process in the pathogenesis of several inflammatory, autoimmune and malignant diseases. Endothelial damage and inflammation make a significant contribution to the pathophysiology of β-thalassemia.Purpose: The aim of the study was to assess serum VEGF level in children with beta-thala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…This was proved by Fahmey et al who reported that there was a significant correlation between platelets count and serum level of VEGF in beta thalassemia major [16] .…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…This was proved by Fahmey et al who reported that there was a significant correlation between platelets count and serum level of VEGF in beta thalassemia major [16] .…”
Section: Discussionmentioning
confidence: 76%
“…Fahmey et al reported that VEGF level was also higher in splenectomised thalassemic patients than non-splenectomized ones (p=0.001) [16] .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations